The Province of Jambi's Madrasah Education Development Strategy: Integrating Contemporary and Conventional Methods - Pitri, Alisyah; Nilfatri, Nilfatri; Othman, Nooraini; Ghufron, M. Ali (Zabags International Journal of Islamic Studies, 2024)
The purpose of this study is to investigate the roles and tactics madrasahs employ in addressing the problems of globalization and curriculum changes, as well as the dynamics of madrasahs in Jambi with an emphasis on social, cultural, and educational changes that take place. With an ethnographic approach, this study employs a qualitative methodology. Because it can give a detailed picture of daily routines, interpersonal relationships, and community culture in madrasahs, this approach was selected. Comprehensive interviews, document analysis, and participant observation were used to gather data. The study's findings demonstrated that proactive curriculum adaptation and sensible management techniques are essential for madrasahs to succeed in surviving and growing in the face of international competition. The parental support system and the role of teachers are the obstacles that must be addressed. To guarantee the caliber of education at madrasahs going forward, it is advised that educators undergo regular review and training